Effect of parenting intervention through "Care for Child Development Guideline" on early child development and behaviors: a randomized controlled trial - Maryam Bemanalizadeh; Negin Badihian; Mehri Khoshhali; Shervin Badihian; Neda Hosseini; Marziye Purpirali; Mansoore Abadian; Omid Yaghini; Seyede Shahrbanoo Daniali; Roya Kelishadi (BMC, 2022)
Abstract Background Several studies showed that parenting intervention programs play a core component in early child development. Considering the limited healthcare resources in developing countries, group-session intervention based on care for child development (CCD) guideline might be cost-effective. Methods This randomized controlled trial was conducted at an outpatient public Pediatrics clinic in Isfahan, Iran. We included 210 pregnant women aged 18-45 years in their third trimester and followed their children for 18 months. The intervention group underwent 5 educational group sessions, each lasting for almost 45 minutes. The main outcomes were the children's development and socio-emotional behavior problems based on Bayley Scales of Infant and Toddler Development-III (BSID-III) at 12 months and the Children Behavior Checklist (CBCL) at 18 months. Results Overall, data of 181 children were included in the current study, including 80 in the intervention group and 101 controls. The adjusted median/mean differences between intervention and control groups using median/linear regression were not significant for all BSID-III domains except for median differences for cognitive score based on BSID-III (β (SE): − 4.98(2.31), p:0.032) and mean differences for anxiety/depression score based on CBCL (β (SE): − 2.54(1.27), p:0.046). Conclusion In this study, parenting interventions through CCD group sessions were significantly effective on just one subscale of children's socio-emotional behavior domains based on CBCL and one domain of children's development based on BSID-III. There might be a ceiling or floor effects for the BSID-III and CBCL assessment, respectively, leaving little room for improvement as almost all children have achieved their full developmental potential in our study. Trial registration IRCT20190128042533N2, Date of registration: 16/01/2020, www.irct.ir